A Continuous Commissioning Analysis and its Application to a New Installed Solar Driven DEC System Coupled with Heat Pump. (May 2015) - Frein, Antoine; Aprile, Marcello; Muscherà, Matteo; Scoccia, Rossano; Motta, Mario
Abstract: The aim of this paper is to define and implement a continuous commissioning methodology that can be effectively applied to a solar driven desiccant and evaporative cooling (DEC) system. The objective is to assess the energy performance of the system's components and identify possible operation faults. The methodology consists in the breakdown and analysis of the DEC into sub-systems; for each of them a simplified dynamic mathematical model based on experimental data has been developed. A possible fault is detected when the difference between the theoretical and measured performances is higher than the accuracy of the methodology. The proposed methodology has been successfully implemented for a hybrid solar DEC system comprising a non-conventional DEC air-handling unit, a solar thermal system and an electrical heat pump. The results of the methodology's application to the first experimental data of summer 2014lead to the following conclusions: the solar sub-system operated as expected whereas the heat pump and the desiccant rotor did not. In particular, the electrical heat pump has a higher cooling capacity than the one predicted at partial load but with a similar COP value, this deviation is mainly due to the assumed partial load performance coefficient. The desiccant rotor presents a much lower performance than the one expected. However, the rotor inefficiency is difficult to highlight due to the high measurement uncertainties on the air side.